2019
DOI: 10.1108/jfc-10-2018-0111
|View full text |Cite
|
Sign up to set email alerts
|

Political connections and corporate social responsibility reporting in Portugal

Abstract: Purpose This paper aims to examine the relation between firms’ political connections and corporate social responsibility (CSR) reporting in Portugal. The authors argue that in settings where the existence of political connections are viewed as damaging collective interests of stakeholders, political connected firms can deal with legitimacy issues from such connections by resorting to CSR practices and the reporting thereof. Design/methodology/approach Using archival data from a panel sample of 36 firms from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 65 publications
2
19
0
15
Order By: Relevance
“…First, this study considers political directors as a heterogeneous group and explores the influence of directors' ideology and regional identity as personal characteristics that determine their decisions on CSR. Thus, our research supports arguments of the legitimacy theory on the positive influence of politicians on CSR, which, beyond the effect on CSR reporting (Fernández-Gago et al 2018;Bianchi et al 2019;Ramón-Llorens et al 2019), has been studied only in the Chinese context. In addition, our study helps to build a theoretical basis for the relationship between liberal political ideology and CSR.…”
Section: Theoretical Contributionssupporting
confidence: 87%
See 2 more Smart Citations
“…First, this study considers political directors as a heterogeneous group and explores the influence of directors' ideology and regional identity as personal characteristics that determine their decisions on CSR. Thus, our research supports arguments of the legitimacy theory on the positive influence of politicians on CSR, which, beyond the effect on CSR reporting (Fernández-Gago et al 2018;Bianchi et al 2019;Ramón-Llorens et al 2019), has been studied only in the Chinese context. In addition, our study helps to build a theoretical basis for the relationship between liberal political ideology and CSR.…”
Section: Theoretical Contributionssupporting
confidence: 87%
“…This is also reflected in the barometer of the Spanish Center for Sociological Research (CIS), which showed how the political class and political parties were the third main problem in the country in January 2011 (after unemployment and economic problems). Therefore, the context is one in which political connections are viewed with suspicion (Ramón-Llorens et al 2019), which may lead to more investment in CSR, given that cajas were forced to demonstrate that, despite this political presence, they met society's expectations (Bianchi et al 2019). Similarly, political directors, whose personal reputation was damaged, could view CSR as an appropriate strategy to improve their reputation in order to achieve personal goals.…”
Section: Institutional Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Davidson et al (2019) discuss that the materialistic managers have lesser concern for others, and are less sensitive to how their actions affect the community and environment. Muttakin et al (2018) suggest that the perceived need for CSR as a legitimation strategy diminishes for politically connected firms, and Bianchi et al (2019) argue that in settings where the existence of political connections are viewed as damaging collective interests of stakeholders, political connected firms can deal with legitimacy issues from such connections by resorting to CSR practices and the reporting thereof. In addition, López-González et al (2019) suggest that family firms have shown to have a singular behavior in terms of CSR, earnings management, and concern for maintaining their reputation.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, Alazzani et al (2019) document that the presence of royal family members on the board of directors is associated with higher levels of CSR reporting in six Gulf Cooperation Council countries including Kingdom of Saudi Arabia, UAE, Bahrain Qatar, Oman and Kuwait. In the same vein, Bianchi et al (2019) document that there is a positive relation between political connections and CSR reporting in Portugal.…”
Section: Political Connection Effectsmentioning
confidence: 93%